The impact of the implementation of the Dutch combined Meeting Centres Support Programme for family caregivers of people with dementia in Italy, Poland and UK. (1st February 2020) - Evans, Shirley; Evans, Simon; Brooker, Dawn; Henderson, Cate; Szcześniak, Dorota; Atkinson, Teresa; Bray, Jennifer; Amritpal, Rehill; Saibene, Francesca Lea; d'Arma, Alessia; Scorolli, Claudia; Chattat, Rabih; et al.
Abstract: Objectives: The MEETINGDEM research project aimed to implement the combined Dutch Meeting Centre Support Programme (MCSP) for community-dwelling people with dementia and caregivers within Italy, Poland and UK and to assess whether comparable benefits were found in these countries as in the Netherlands. Method : Nine pilot Meeting Centres (MCs) participated (Italy-5, Poland-2, UK-2). Effectiveness of MCSP was compared to usual care (UC) on caregiver outcomes measuring competence (SSCQ), mental health (GHQ-12), emotional distress (NPI-Q) and loneliness (UCLA) analysed by ANCOVAs in a 6-month pre-test/post-test controlled trial. Interviews using standardised measures were completed with caregivers. Results: Pre/post data were collected for 93 caregivers receiving MCSP and 74 receiving UC. No statistically significant differences on the outcome measures were found overall. At a country level MC caregivers in Italy showed significant better general mental health (p = 0.04, d = 0.55) and less caregiver distress (p = 0.02, d = 0.62) at post-test than the UC group. Caregiver satisfaction was rated on a sample at 3 months (n = 81) and 6 months (n = 84). The majority of caregivers reported feeling less burdened and more supported by participating in MCSP. Conclusion: The moderate positive effect on sense of competence and the greater mental health benefit for lonely caregivers using the MCSP compared to UC as found in the original Dutch studies were not replicated. However, subject to study limitations, caregivers in Italy using MCSP benefitted more regarding their mental health and emotional distress than caregivers using UC. Further evaluation of the benefits of MCSP within these countries in larger study samples is recommended.